Inguinal ulcerated sebaceous carcinoma: an unusual presentation - David Oschilewski Lucares; Fred Bernardes Filho; Hernando Vega; Bernard Kawa Kac; Maria Rita Pereira; José Augusto da Costa Nery (Sociedade Brasileira de Dermatologia, 2013)
Sebaceous carcinoma is a rare and aggressive skin tumor. It can be located in any area of the body, the most commonly involved area being the periorbital region. It does not entail a typical clinical presentation, which explains the often late diagnosis. The aim of this report is to outline the rarity of the disease and its atypical clinical description, since to this day, inguinal ulcers with clinical manifestation have not been reported. We present and discuss a case of sebaceous carcinoma with an unusual clinical presentation, in an elderly male patient. The precise approach to genital ulcers, as shown in this case, is a diagnostic challenge that requires a great deal of effort on the part of the clinician.